Avalanche solar blind photodetectors based on single crystalline Mg0.47Zn0.53O thin film on Ga:ZnO substrate. (5th April 2018) - Chen, Hao; Zhang, Jingtao; Chen, Zuxin; Liu, Huiqiang; Ma, Xinzhou; Li, Qiuguo; Chu, Guang; Chu, Sheng
Abstract: Single crystalline wurtzite Mg0.47 Zn0.53 O films were grown on Ga:ZnO substrates by pulse laser deposition. The band gap of the films was measured to be 4.43 eV. Vertical devices were fabricated for solar blind photodetection, realizing a high responsivity of 2 A W −1 at 278 nm and  −5 V bias as well as a rejection ratio ( R 278 nm / R 350 nm ) of over 6  ×  10 3 . A cut-off wavelength of 286 nm and a response time of 77 ms were also achieved. Besides, the devices showed stable response without degeneration under repeating illumination. The high performance of this photodetector was analyzed and attributed to the avalanche effect from high quality Mg0.47 Zn0.53 O/Ga:ZnO heterojunction at reverse bias. The avalanche gain was calculated to be 14.5 at  −10 V.